Barley varieties registered in the Czech Republic after the harvest of 2023 - Psota, Vratislav; Dvořáčková, Olga; Garčárová, Markéta; Boško, Rastislav (KVASNY PRUMYSL, 2024)
After the 2023 harvest, four varieties of spring barley were registered in the Czech Republic. The malting quality was determined in three varieties. After four years of testing, LG Tuplak was registered. After three years of testing, the spring barley varieties LG Lokal, Sting, and the non-malting variety Ranee were registered. LG Tuplak and LG Lokal showed low activity of proteolytic and cytolytic enzymes and a low level of apparent final attenuation and thus fulfilled the conditions for varieties recommended for the production of beer with the protected geographical indication 'České pivo'. The spring barley variety Sting showed very good malting quality. It provided a sweet wort with a rich extract content in malt dry matter (above 83%). Proteolytic modification was optimal to higher in this variety. Cell wall degradation was at an optimal level in the Sting variety. The varieties tested gave clear to opalescent sweet wort.